Network Education and Blended Learning: Cyber University concept and Higher Education post COVID-19 Pandemic (Research, Society and Development, 2020)
Educational processes, over the past few years, are changing due to the various changes that society has been going through, driven by the insertion of the internet in daily life. The present study presents an essay on the perspectives for Higher Education from the pedagogical practices developed during the period of the COVID-19 pandemic. Concepts such as Network Education and Hybrid Education bring to light the reflection on the physical and virtual place of the university, involving economic issues that would make higher education courses cheaper in a virtual modality. Based on an exploratory research, outlined in a bibliographic way, the validity of the thesis about a paradigm shift for Higher Education, built under a hybrid model, was investigated. It is concluded that experiencing the university, from a social point of view, is very relevant, in addition to the accumulation of knowledge without articulation with everyday life, and that Hybrid Teaching is a methodological alternative in the establishment of the Network Education process, effective from Active Methodologies.